Gestão da saúde e segurança, qualidade de vida no trabalho e gestão da diversidade como elementos do pilar social da sustentabilidade organizacional: um estudo sobre as práticas nas 150 melhores empresas para se trabalhar no Brasil - Sierdovski, Marcia (2018)
Elkington (2012) highlights the concern that organizations need to have with human capital, their way of life, their health, their education and acquired skills, extending to discussions of social, ethical and political themes. This concern with the individual who works was measured by the variables of health and safety management, quality of life at work and management of diversity. In this context, the research problem of this dissertation was to investigate: how do we present the elements of the social pillar of sustainability, based on strategy as a practice in the management of health and safety, quality of life at work and diversity management, in the 150 best companies to work in Brazil? The objective of the research was to analyze strategy as a practice in health and safety management, QWL and diversity management as elements of the social pillar of organizational sustainability in the 150 best companies to work in Brazil. With regard to the methodological procedures, this research is characterized as descriptive, with a quantitative approach, the data collection was carried out through questionnaires sent electronically to the employees of 150 companies that were considered the best to work in Brazil in 2016, to find out their opinions on people management practices and their happiness index at work. These practices will be measured on a 5-point likert scale by performing descriptive statistical tests such as mean, standard deviation, Cronbach's alpha, Spearman's correlation test, and the Qui-square test. Thus, this research sought to analyze the contribution of social practices to personal and professional satisfaction, quality of life and workers' organizational well-being. The results in the descriptive statistical tests point out that in the strategy as a social practice the employees affirm that working in the best companies has made their lives better, they feel happy and their lives become better. In the health and safety management element, the employees' most perceived and well-evaluated practice refers to the importance that the products and services provided by these companies have for our society. In the element of quality of life at work, practice is conditioned to the pride of telling friends that they belong to this corporation. In the element of diversity management, the considered practice is that people of any age, race, color and sexual orientation are treated with the same justice and respect in the organization. In the Spearman correlation tests, it was verified that all variables studied as elements of analysis of the social pillar of sustainability were positive for their correlation coefficients, being classified from weak correlation, but defined until a high moderate correlation. The most important element was the variable of quality of life at work, with the agreement of the practice that the company uses fair criteria for promotion and career. In the Qui-square test that compared to the sociodemographic profile, some characteristics were given such as age, education, income and position, being these characteristics of great influence for the accomplishment, satisfaction, attendance of needs and happiness of the collaborator.